The Devadasi, dharma and the state - Nair, Janaki (1994)
The article gives us a bird's eyeview of the conditions present within the Chinese bureaucracy including administrative, ideological, and legal constraints. Also discussed are the means used by the Chinese government to counter corruption
Keywords: Devadasis - India; Women - India